2021
DOI: 10.1155/2021/1093412
|View full text |Cite
|
Sign up to set email alerts
|

Central Odontogenic Myxoma: A Radiographic Analysis

Abstract: Objective. This study aimed to determine the radiographic characteristics of odontogenic myxomas (OMs) and their associations. Materials and Methods. The study enrolled radiographs of patients taken between 2005 and 2019 with a confirmed histopathological diagnosis of central OM. OM radiographic features were evaluated, including location, border, locularity, involved area, the number of included teeth, root resorption, tooth displacement, bone expansion, bone perforation, and periosteal reaction. Fisher’s exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…8 Additionally, despite being locally aggressive, anterior OMs seldom cross the midline, and if found to be doing so, are again usually those occurring in the maxilla. In this aspect, our case of OM crossing the midline in the mandibular anterior region is quite a rare occurrence and was similar to a case reported by Ghazali et al 5 A lesion appears to be multilocular when the septae of bone are left while the surrounding medullae are resorbed by the active disease process. OM being nonencapsulated and highly aggressive, substantial infiltration occurs in the adjacent medullary bone owing to the action of hyaluronidase that resorbs hyaluronic acid proteoglycan in the extracellular matrix.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…8 Additionally, despite being locally aggressive, anterior OMs seldom cross the midline, and if found to be doing so, are again usually those occurring in the maxilla. In this aspect, our case of OM crossing the midline in the mandibular anterior region is quite a rare occurrence and was similar to a case reported by Ghazali et al 5 A lesion appears to be multilocular when the septae of bone are left while the surrounding medullae are resorbed by the active disease process. OM being nonencapsulated and highly aggressive, substantial infiltration occurs in the adjacent medullary bone owing to the action of hyaluronidase that resorbs hyaluronic acid proteoglycan in the extracellular matrix.…”
Section: Discussionsupporting
confidence: 89%
“…OM has been reported to occur mostly in patients within the age range of 21 to 51 years and a mean age of 31 to 32.4 years has been described. 1,5 While some databases have reported no sexual predilection, some investigators have found that a greater number of cases of OM have occurred in females. 7 Most of the cases do not present any clinical symptoms or at most with only swelling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations